Analysis of the effect of job satisfaction on millennial employee turnover intention - Aulina, Fatimah; Putri, Santika (Yayasan Cinta Negara Indonesia, 2025)
This study analyzes the effect of job satisfaction on turnover intention among millennial employees, a workforce segment increasingly dominating organizational structures. The millennial generation is often characterized by high career mobility, distinct workplace expectations, and strong value orientation toward meaningful work–factors that can influence their decision to remain in or leave an organization. Using a quantitative approach, primary data were collected through a structured questionnaire distributed to 215 millennial employees across various industries in urban areas. Job satisfaction was measured across key dimensions including work environment, compensation, career development, leadership style, and work–life balance, while turnover intention was assessed through indicators of withdrawal cognition, job search behavior, and intention to quit. The data were analyzed using multiple linear regression to determine the strength and significance of the relationship between job satisfaction and turnover intention. The findings reveal a statistically significant negative relationship between job satisfaction and turnover intention (p < 0.05), indicating that higher job satisfaction leads to a lower likelihood of turnover intention among millennial employees. Among the satisfaction dimensions, career development opportunities and leadership style emerged as the most influential factors. These results underscore the need for organizations to design employee engagement strategies tailored to the values and expectations of millennials. By enhancing job satisfaction, employers can reduce turnover risk, retain talent, and maintain organizational stability in an increasingly competitive labor market